Tumor characteristics and treatment outcomes of older patients with breast cancer in Jordan - Hikmat Abdel-Razeq; Fadwa Abdel Rahman; Hanan Almasri; Hazem Abdulelah; Mahmoud Abunasser; Mourad Salam; Ayat Taqash (BMC, 2020)
Abstract Background Less than 10% of newly diagnosed breast cancer cases in Jordan are diagnosed in women 70 years or older. Treatment plans of such patients is less clear and could result in poor outcomes. In this paper, we describe clinical presentation, tumor characteristics and treatment outcomes in this population of breast cancer patients. Methods Consecutive patients aged 65 years or older with pathologically-confirmed diagnosis of breast cancer were included. Medical records and hospital databases were searched for patients' characteristics and treatment outcomes. Results A total of 553 patients, mean age ± SD (71 ± 5.1) years, were included. On presentation, 114 (20.6%) patients had metastatic disease and was mostly visceral (81; 71.1%). Patients with non-metastatic disease had poor pathological features including node-positive in 244 (55.6%), high grade (grade III) in 170 (38.7%) and lymphovascular invasion in 173 (39.4%). Patients were treated less aggressively; 144 (32.8%) patients with early-stage disease and 98 (86.0%) with metastatic disease never had chemotherapy. After a median follow up of 45 months, 5-year overall survival for the whole group was 67.6%. Survival was better for patients with non-metastatic disease (78.8% vs. 25.4%, P < 0.001) and for those with node-negative compared to node-positive disease (85.4% vs. 74.1%, P = 0.002). On Cox regression, only positive lymph nodes were associated with poor outcome in patients with non-metastatic disease (Hazard Ratio [HR], 1.75; 95% CI: 1.006-3.034, P = 0.048). Conclusions Older Jordanian patients with breast cancer present with more aggressive features and advanced-stage disease that reflect poorly on treatment outcomes. Older patients were treated less aggressively with less than a third received any chemotherapy.